Prevalence of malnutrition and its determinants in an elderly people in South India - Konda, Satyanarayana; B. P., Ravi Kumar; Giri, Purushottam A (International Journal Of Community Medicine And Public Health, 2018)
Background: The population of elderly people aged ≥60 years is increasing worldwide and is projected to reach 1.5 billion by 2050. In India, the elderly people constitute 8.1% of the total population. Malnutrition is highly prevalent in the elderly population due to various diseases and impairments. Methods: A cross-sectional study was carried out amongst 209 elderly people from February 2018 to April 2018. A questionnaire was used to collect data related to socio-demographic characteristics, Mini Nutritional Assessment (MNA) and regarding medication use, comorbidity, use of a walking aid, smoking and alcohol consumption. The MNA tool was used for the assessment of nutrition status. For an assessment of functional status, the activities of daily living scale and instrumental activities of daily living scale were used. Descriptive analysis and Chi-square test were used to present the data. Results: The average MNA score was 23.5 (SD=4.3, range: 7-30) and that of BMI was 23.8 (SD=3.9, range: 15.6-38.9). Of 209 study participants, 9.1% were malnourished, 32.5% were at risk of malnutrition and remaining 58.4% were having normal nutritional status. The possible predictors of malnutrition were older age, lower education level, staying single, unemployed, low income and less than three meals daily. Conclusions: The overall prevalence of malnutrition was found to be 9.1% but the proportion of elderly people at risk of malnutrition was relatively high. Diagnosis and treatment of elderly people at high risk for malnutrition based on the findings of this study may improve functional status and prognosis of elderly people.